Effect of Internal Carotid Artery Stenting on Superior Thyroid Artery Doppler Flow. (1st October 2014) - Gunduz, Yasemin; Akdemir, Ramazan; Varim, Perihan; Ayhan, Lacin Tatli; Cakar, Mehmet Akif; Vatan, Mehmet Bulent; Kilic, Harun
Abstract : Objectives: Patients with carotid disease are frequently referred for carotid artery stenting based on the results of carotid duplex studies. During carotid artery stenting, the stent is usually extended into the common carotid artery, thereby crossing the external carotid artery. Previous studies have shown conflicting results regarding internal carotid stenting and external carotid artery flow velocities, but the effect of stenting on ipsilateral superior thyroid artery velocities has not been defined. This study examined the effect of internal carotid angioplasty and stenting on the ipsilateral superior thyroid artery Doppler‐derived flow parameters. Methods: We prospectively studied preinterventional and postinterventional duplex scans obtained from 41 patients (mean age ± SD, 64 ± 10 years) who underwent carotid artery stenting. The Doppler‐defined preprocedural peak systolic velocity (PSV) end‐diastolic velocity (EDV), resistive index (RI), and pulsatility index (PI) in the ipsilateral external carotid and superior thyroid arteries were compared with postprocedural values. Results: Among patients with stenting, the preprocedural PSV, EDV, RI, and PI in the ipsilateral superior thyroid artery were 30 ± 11 cm/s, 13 ± 6 cm/s, 0.62 ± 0.11, and 1.04 ± 0.28, respectively; after stenting, they were 36 ± 8 cm/s, 14 ± 9 cm/s, 0.71 ± 0.07, and 1.11 ± 0.19. The preprocedural PSV, EDV, RI, and PI in the ipsilateral external carotid artery were 79 ± 24 cm/s, 17 ± 7 cm/s, 0.77 ± 0.26, and 1.27 ± 0.22; after stenting, they were 94 ± 31 cm/s, 20 ± 6 cm/s, 0.80 ± 0.4, and 1.25 ± 0.31. Despite a slight increase in superior thyroid and external carotid artery flow, there was no statistically significant change from before to after stenting. Conclusions: This study showed no differences in blood velocity profiles in the ipsilateral superior thyroid and external carotid arteries after stenting.